Evoliucinė medicina: žmogaus raidos perspektyvos ir sveikata besikeičiančioje aplinkoje. Septintoji tarptautinė konferencija - Tutkuvienė, Janina; Morkūnienė, Rūta; Jakimavičienė, Eglė Marija (Vilnius University Proceedings, 2026)
This Abstract Book presents the scientific contributions of the 7th International Conference “Evolutionary Medicine: Perspectives on Human Development, and Health Consequences in a Changing Environment”, held at Vilnius University, Vilnius, Lithuania, on July 7–10, 2026. The conference brings together researchers, PhD students, undergraduate students, clinicians, educators and other professionals interested in human development, growth, maturation, health and disease from an interdisciplinary perspective. This volume includes the abstracts of more than 100 scientific presentations, reflecting both the main thematic focus of the conference and the broad diversity of research fields represented by its participants.The 7th International Conference on Evolutionary Medicine consists of two parts. The first part is dedicated to the main topic of the conference and focuses on evolutionary medicine, auxology, growth and maturation, and the long-term health consequences of developmental processes in a changing environment. By addressing the relationships between growth, life history and health trajectories, this thematic part of the conference aims to deepen our understanding of human biological variation, adaptation and vulnerability in changing environmental, social and cultural contexts.The thematic focus of the first part of the conference has deep historical roots at Vilnius University. This conference commemorates the 220th anniversary of the first auxological works at the University. In 1805, the “Dziennik Wileński” published Andrzej (Jędrzej) Śniadecki’s work on child development and physical education. A. Śniadecki, Professor of Chemistry and later Head of the Department of Medicine at Vilnius University, was a distinguished scholar whose work connected medicine, biology, hygiene, dietetics, education and philosophy. In the context of evolutionary medicine and auxology, his work “On the Physical Education of Children” is particularly relevant, as it addressed the growth and maturation of children within a broad psychosocial and lifestyle-related context, including physical activity, nutrition, sleep, hygiene, and the balance between mental and physical work.The second part of the conference provides a broader interdisciplinary platform for doctoral students, young researchers and other scientists to present their research, including topics not necessarily directly related to evolutionary medicine or auxology. The aim of this part is to promote scientific communication, dissemination of research results, academic exchange and cooperation in various scientific fields. Representatives of medicine, health sciences, natural sciences, social sciences, technological sciences and humanities are invited to participate. The conference aims to strengthen interdisciplinarity and create opportunities for young researchers to develop presentation skills, broaden their scientific perspective, and establish dialogue with colleagues from various academic backgrounds. The organizers hope that this book of abstracts will be of interest not only to researchers in human biology, evolutionary medicine, auxology, pediatrics, and public health, but also to educators, students, and professionals in other scientific fields. The conference aims to promote evolutionary thinking, expand understanding of human biology, and foster fruitful collaboration across many different scientific fields.